A Plant Simulation Approach Applied Sequencing Strategies for Buffer Prediction: A Case Study in an Automotive Assembly Line - Butrat, Anan (Thai Journal of Science and Technology, 2024)
In this study, a plant simulation approach to buffer prediction for an automotive assembly line was proposed. Currently, the assembly line has exceeded the buffer size. The idea to reduce buffer size is to increase worker size and sequencing strategy. With simulation, two approaches, including throughput analysis and production time analysis, are proposed. The throughput analysis can find the required buffer sizes for maximizing throughput when the total available time is used. The production time analysis can determine the time spent using each buffer space with a fixed throughput size. In terms of results, the sequencing strategy that produces two normal models and one new model provides the first plan to implement. Without increasing worker size, this strategy can finish 48 cars per shift by using 8 buffer spaces. Moreover, increasing one worker is the second plan so that the throughput of this strategy can reach 58 cars per shift. Additionally, this simulation model highlights the modified Blocking After Station (MBAS) that can define not only buffer usage but also the buffer requirement. This research offers a simulation approach to the prediction of buffet usage and the requirement to define an action plan for an unfamiliar task in the automotive assembly line.